STATUS AND DISTRIBUTION OF THE WILD TURKEY IN 1999 - Jennifer L. Tapley; Robert K. Abernethy; James E. Kennamer (Wildlife Society Bulletin)
Abstract: Wild turkey (Meleagris gallopavo) populations in North America have increased steadily in the last 45 years since restoration began in earnest. This increase is the result of intensified restoration efforts, improved habitat conditions and increased protection. A survey of wild turkey populations was first published in the 1959 Proceedings of the First Wild Turkey Symposium. Similar surveys have been made every 5 years since 1970 and the results published in all but one of the subsequent wild turkey symposia. We describe the current distribution of wild turkeys in North America. We surveyed state and provincial wildlife agency biologists responsible for wild turkey programs in 1999 to determine the status of the bird in their jurisdiction. We report population estimates by subspecies, compare current occupied range to that of 5 years ago, and report on the status of each state or province's restoration program. Wild turkey populations have increased by almost 1.3 million birds in the past 5 years, and in 1999 are estimated at 5.4 million birds.